ReFlex gamification for cerebral palsy kids - Ahmad Firdaus, Ilias; Mohd Azrul Hisham, Mohd Adib; Muhammad Nor Hakim, Hassan; Muhammad Mirza, Mustapah; Muhammad Alif Aiman, Jamaludin; Sheh Hong, Lim (2021)
The available device in the market nowadays does not have a specific function on active movements, especiallay active range of motion (arom), where the movement of a joint provided entirely by the individual performing the exercise. most rehabilitation device needs full involvement of psysiotherapists during the rehabilitation session